SPECIFICITY OF COGNITION OF SOCIAL RELATIONS - Мокляк, Н. Н.; Мокляк, Л. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Peculiarities of cognition and improvement of social relations are analyzed in the article.